Study on Black Hole Information Paradox from the Viewpoint of the Discrete Time Hypothesis - Zaslavsky, Alexander M. (Newest Updates in Physical Science Research Vol. 11, 2021)
Based on the discrete time hypothesis, the phenomenon of phase substitution of the wave function of a particle falling in a black hole is considered. The results speak for possibility of certain exotic forms of the wave function evolution, providing among other things, return of information when the particle is falling down to a static black hole. When substitution the phase of the wave function in the vicinity of the event horizon, information may return due to the local reversal of particle time. Based on the analysis of the flow of information returned, using the holographic principle, an estimate of the quantum of the particle’s proper time is obtained.